2000
DOI: 10.1002/1097-4628(20001107)78:6<1304::aid-app160>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of solute organic compounds and water in poly(dimethylsiloxane)

Abstract: The properties of an aqueous solution are interesting depending on its application. Their characteristics are mainly a result of a hydrophobic interaction. The permeation behavior, particularly for an aqueous solution with a hydrophilic solute, is affected by the hydration of water to the solute. In case of an aqueous solution of organic compounds, generally, the water molecule adjacent to the solute become less mobile than in the pure water due to hydration. The hydration may affect the diffusivity of solute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Membrane techniques for the removal of VOCs in water can offer potential savings in energy costs. Many studies have been reported on the permeation and removal of VOCs from water by various hydrophobic polymer membranes, mainly composed of poly(dimethylsiloxane) (PDMS),18–28 zeolite‐filled PDMS,29,30 and various other materials 31–33…”
Section: Introductionmentioning
confidence: 99%
“…Membrane techniques for the removal of VOCs in water can offer potential savings in energy costs. Many studies have been reported on the permeation and removal of VOCs from water by various hydrophobic polymer membranes, mainly composed of poly(dimethylsiloxane) (PDMS),18–28 zeolite‐filled PDMS,29,30 and various other materials 31–33…”
Section: Introductionmentioning
confidence: 99%
“…Its glass transition temperature is among the lowest values recorded for polymers (−129°C) indicating a very flexible polymer backbone with long‐range segmental motion active event at very low temperatures 16–18. As a result, PDMS‐based membranes usually have a relatively higher flux for organics than glass‐state membranes 16, 19–22. Currently, PDMS elastomer is the most commonly used membrane material for the separation of organic vapors from permanent gases 3…”
Section: Introductionmentioning
confidence: 99%
“…Unlike activated carbon, the separating medium does not require frequent replacement and disposal. Among common organophilic polymers, poly dimethylsiloxane (PDMS) has been proven to have the best performance in the pervaporative removal of volatile organic compounds (VOCs) from their dilute aqueous solutions by many researches 11–14. PDMS exhibits relatively high permeability and is ideal for VOCs to pass through because of the flexible molecule chains and high‐free volume.…”
Section: Introductionmentioning
confidence: 99%